UOL TAB: a inovação na reportagem multimídia? análise das características e elementos das narrativas jornalísticas na web - COSTA, Marina Gama (2021)
Journalism is a practice that has developed with society. The great journalistic narratives have assumed several characteristics since the first writings, of the printed and, more today, with digital devices. With technological changes and the emergence of new tools and practices of interaction with resources in constant transformation, the experiences of individuals have also reshaped and adapted to this reality. Using as a theoretical contribution that discusses the concepts and characteristics of the great journalistic narratives, multimedia and convergent journalism, the central objective of this research is to investigate the extent to which the content of the UOL TAB fits into the attributions of multimedia reporting, as it has been characterized since the beginning of its work. For this it was necessary to observe the characteristics of these products based on the theoretical framework studied from the concepts of Magno (2006), Lima (2009), Sodré and Ferrari (1986) and Ijuim (2017), dealing with the report and its characteristics; and Jenkins (2009), Longhi (2010, 2014, 2015), Longhi and Flores (2017) and Ferrari (2019), dealing with convergence and multimedia narratives. Applying its concepts in the corpus of analysis selected for this study: the three weekly productions of May 2019 and the six weekly productions of May 2020, totaling nine reports to be analyzed, the cut-out defined for analysis and comparison takes into account a part of the covid-19 pandemic period. The delimitation in these two months occurs for the observation of how the productions are presented in two periods with such different contexts, from the structure of the reports, the elements used in their composition, to the approach of themes and other characteristic factors of journalistic narratives. We come to the facts: the TAB is by nature a multimedia content platform. However, given the diversity of characteristics pointed out throughout the research, it is worth highlighting some observations and criticisms about the observed narratives. Features such as interactivity and exploration of other media that could better assist in storytelling are points that need to be taken into account.